Comunicação e cidadania às margens do São Francisco: os correspondentes populares da Diocese de Juazeiro Ba (19882008) - Oliveira, Roberto Joaquim de (2008)
This thesis presents a case study, supported by research literature, documentary research and semistructured interview about the work of popular correspondents in Setor de Comunicação e Audiovisual (SEDICA) of the Juazeiro s Diocese in Bahia, between the years 19882008 . The Main goal is to analyze the development of experience, taking into account their community character level, the relationship between the various partners in the processes of communication and the meaning that have the experience to the correspondents involved. It was evident that the work of SEDICA deserves attention because remain as an option communication that values the listeners, and from them, builds a schedule of critical and participatory character. His connection with the reality of the diocese is guaranteed because their sources living a hard life in semiarid northeastern that brings what the programs content of the residents, which outweigh the difficulties in a creative way, as the corresponding overcome their difficulties in the production news that must periodically submit to the sector of communication.(AU)